A cross-linked starch-based biodegradable plastic and preparation method thereof
By grafting reaction with oxidized sweet potato starch using hyperbranched polyamide polyamine crosslinking agent, hyperbranched crosslinking starch is formed, and mixed with polypropylene powder extrusion, the problem of insufficient flame retardant and mechanical properties of existing starch-based plastics is solved, and high-performance biodegradable plastics are achieved.
Patent Information
- Application Number
- CN202411143731.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing starch crosslinking agent has poor compatibility with starch and low crosslinking degree, resulting in insufficient flame retardant and mechanical properties of starch-based plastics.
Hyperbranched polyamide polyamine crosslinking agent and oxidized sweet potato starch are grafted to form hyperbranched crosslinking starch, and mixed with polypropylene powder in a high-speed kneader and twin-screw extrusion granulation equipment to prepare crosslinked starch-based biodegradable plastic.
The flame retardant and mechanical properties of starch-based plastics are significantly improved, and biodegradable plastics with good mechanical properties and flame retardant properties are formed.
Smart Images

Figure BDA0005001650000000051 
Figure BDA0005001650000000052 
Figure BDA0005001650000000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modified starch, in particular to a cross-linked starch-based biodegradable plastic and a preparation method thereof. Background Art
[0002] As a new type of lightweight chemical material, plastic products have penetrated into all aspects of life. However, since plastic products made from traditional petroleum-based plastics have a long degradation period and are prone to "white pollution", the large-scale use of disposable non-degradable plastic products has a great negative impact on the soil and environment, seriously damaging the environment and endangering human health. Therefore, the development and promotion of environmentally friendly biodegradable materials is an urgent need to alleviate the current environmental and ecological pressure. Starch, as a natural polymer compound, has the advantages of wide sources, low prices and renewability, and can be completely degraded in the natural environment. Therefore, from the perspective of reduction and resource replenishment and substitution, its development has received great attention.
[0003] Starch is a natural polysaccharide with the advantages of being cheap, easily available and biodegradable, but its strong hydrophilicity leads to poor mechanical properties of starch plastics, which need to be blended with some polymer materials for modification. Traditional polymer materials have poor compatibility with starch, and compatibilizers need to be added to increase the compatibility and interfacial strength of the two. Generally, organic acids or acid anhydrides are used to replace, esterify or acetylate the hydroxyl groups in starch molecules, which can significantly improve water resistance and strength. In addition, cross-linking modification of starch is also an effective method. Cross-linking agents (such as glutaraldehyde, citric acid, boric acid, etc.) can form a spatial network structure with the hydroxyl groups of starch through diether bonds or ester bonds. However, starch particles are partially crystalline structures, and the intermolecular hydrogen bonds are strong. When they are subjected to heat and force at the same time, the fluidity is extremely poor and processing and molding are difficult, which reduces the compatibility of starch with other polymer resins, poor thermoplasticity, and cannot be processed by thermoplastic processing such as melt extrusion, making it difficult to use as a polymer material alone.
[0004] In the prior art, traditional plasticizers such as glycerol compatibilizer or acetyl tributyl citrate used for plasticizing starch have poor compatibility with polymer materials and are easy to precipitate. In addition, plasticizers can cause the blended polymer materials such as polypropylene (PP) and polylactic acid (PLA) to become soft or brittle. Traditional cross-linked starches mostly use sodium metaphosphate, glutaraldehyde, etc. as cross-linking agents, but the cross-linked modified starches are mostly directly connected structures, and their mechanical, flame retardant and rheological processing properties cannot meet the needs of actual production. The present invention aims to combine the company's existing high-speed kneading machine with twin-screw extrusion granulation equipment to prepare a hyperbranched polyamide polyamine cross-linking agent mixed with starch and bio-based plasticizers, prepare starch-based plastics through high-speed kneading dry blending and extrusion granulation technology, and significantly improve the flame retardant and mechanical properties of starch-based plastics. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a cross-linked starch-based biodegradable plastic and a preparation method thereof, solve the problems of poor compatibility of the existing starch cross-linking agent with starch and low cross-linking degree, and significantly improve the flame retardant and mechanical properties of the starch-based plastic.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a cross-linked starch-based biodegradable plastic is carried out according to the following steps:
[0008] Step (1), placing oxidized sweet potato starch and deionized water in a three-necked flask, stirring evenly, adding anhydrous sodium sulfate, sodium hydroxide and a hyperbranched polyamide polyamine crosslinking agent, stirring to react, after the reaction is completed, adjusting the pH of the system to neutral, filtering, washing, drying and crushing to obtain a hyperbranched crosslinked starch.
[0009] Step (2), mixing polypropylene powder and hyperbranched cross-linked starch uniformly, placing them on a high-speed kneader for blending, the mixing temperature is 175-190° C., the screw speed is 80-100 r / min, the screw diameter is 10-15 mm, adding them to a twin-screw extruder for extrusion granulation, and then placing them in an injection molding machine for injection molding, the injection molding machine melt chamber temperature is 180-200° C., and the injection time is 5-10 s, to obtain a cross-linked starch-based biodegradable plastic.
[0010] Preferably, in step (1), the ratio of oxidized sweet potato starch, deionized water, anhydrous sodium sulfate, sodium hydroxide, and hyperbranched polyamide polyamine crosslinking agent is 100 g: (200-350) mL: (7-10) g: (0.8-1.2) g: (0.5-2.5) g.
[0011] Preferably, in step (1), the reaction temperature is 45-60° C. and the reaction time is 2-5 h.
[0012] Preferably, in step (2), the ratio of polypropylene powder to hyperbranched cross-linked starch is 100 g:(30-50) g.
[0013] Preferably, the preparation method of the hyperbranched polyamide polyamine crosslinking agent in step (1) is carried out according to the following steps:
[0014] Step S1, under a nitrogen atmosphere, add 4-nitrobenzene phosphorus dichloride and acetonitrile to a reaction flask, stir evenly, add 4-nitroaniline and triethylamine, stir to react, after the reaction is completed, add dimethyl sulfoxide and deionized water to precipitate, filter, wash with ethanol, and dry to obtain a trinitrophenyl phosphorus nitrogen flame retardant monomer.
[0015] Step S2, under a nitrogen atmosphere, add trinitrophenylphosphine nitrogen flame retardant monomer and ethanol into a reaction flask, stir evenly, add palladium carbon and hydrazine hydrate, react at 75-90° C. for 3-8 hours, concentrate under reduced pressure, and recrystallize from ethanol to obtain triaminophenylphosphine nitrogen flame retardant monomer.
[0016] Step S3, under a nitrogen atmosphere, add triaminophenylphosphine flame retardant monomer and N,N-dimethylacetamide to a reaction flask, stir evenly, add 3,3'-iminodipropionic acid, first react at 125-140° C. for 2-4 h, then react at 160-180° C. for 5-12 h, and concentrate under reduced pressure to obtain a hyperbranched polyamide polyamine crosslinker.
[0017] Preferably, in step S1, the ratio of 4-nitrobenzene phosphorus dichloride, acetonitrile, 4-nitroaniline and triethylamine is 1 g: (10-20) mL: (1.1-1.25) g: (0.9-1.2) g.
[0018] Preferably, in step S1, the reaction temperature is 65-80° C. and the reaction time is 8-16 h.
[0019] Preferably, in step S2, the ratio of trinitrophenylphosphine nitrogen flame retardant monomer, ethanol, palladium carbon, and hydrazine hydrate is 1 g: (25-40) mL: (0.05-0.1) g: (2.5-3.5) mL.
[0020] Preferably, in step S3, the ratio of triaminophenylphosphine nitrogen flame retardant monomer, N,N-dimethylacetamide, and 3,3'-iminodipropionic acid is 1 g: (5-10) mL: (0.65-0.9) g.
[0021] Compared with the prior art, the present invention has the following beneficial technical effects:
[0022] The invention firstly reacts 4-nitrobenzene phosphorus dichloride and 4-nitroaniline under the action of triethylamine to obtain trinitrobenzene phosphorus nitrogen flame retardant monomer, then reduces the nitro group to obtain triaminophenyl phosphorus nitrogen flame retardant monomer, then polymerizes with 3,3'-iminodipropionic acid to obtain hyperbranched polyamide polyamine crosslinking agent, then grafts with oxidized sweet potato starch to obtain hyperbranched crosslinked starch, and finally mixes with polypropylene powder in a high-speed kneader and a twin-screw extrusion granulation device for extrusion to obtain crosslinked starch-based biodegradable plastic.
[0023] Hyperbranched cross-linked starch is a three-dimensional tree-like hyperbranched macromolecule. Multiple amino groups in its structure can undergo grafting reaction with the aldehyde groups on the surface of oxidized sweet potato starch to form a dense three-dimensional cross-linked spatial network structure, which makes the starch tightly connected together. Its structure contains phosphorus and nitrogen synergistic flame retardant elements, which can produce polyphosphoric acid during thermal degradation and cover the surface of the polymer matrix. At the same time, a large number of terminal amino groups decompose under heat to produce NH3, which promotes the expansion of the matrix. A large number of substances with benzene ring structures undergo cross-linking reactions to form a high-strength carbon layer with a graphite structure and aromatic ring structures bridged by POP bonds. It can bind a large amount of gas generated during the combustion process, so that the matrix will not expand excessively and produce cracks during the combustion process. In addition, this compact and stable carbon layer can effectively isolate the unburned matrix from the external heat source, hinder the heat exchange between the matrix and the outside world, thereby inhibiting the continued combustion of the polymer and improving the flame retardant properties.
[0024] The hyperbranched polyamide polyamine crosslinking agent itself has good mechanical properties and can significantly enhance the mechanical properties after crosslinking with starch. The multiple amino groups in its structure can crosslink with the aldehyde groups on the surface of oxidized sweet potato starch. The increase in the degree of crosslinking makes the molecular chains arranged in a tight area, the porosity decreases, the hydrophilicity of the starch weakens, and the compatibility with the polypropylene material is enhanced and the binding force increases. When the material is subjected to external forces, it can absorb more impact energy, so that the mechanical properties of the plastic are enhanced; the increase in the degree of crosslinking promotes the combination of starch and polypropylene, increases the overall hydrophobicity of the material, reduces the water absorption rate of the plastic, and can maintain the stability of the size and mechanical properties, which is very beneficial for various applications.
[0025] The present invention prepares starch-based plastics through high-speed kneading dry blending and extrusion granulation processes, and has excellent mechanical, water-resistant and rheological processing properties. The prepared cross-linked starch is also suitable for blending and modification of materials such as PBAT, PLA, and PE, has a wide range of applications, and the amount of addition can be adjusted. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0027] Preparation of oxidized sweet potato starch: Take 360g of dried corn starch, add 500mL of deionized water, stir evenly, adjust the pH to 9.0 with a 5% by mass sodium hydroxide aqueous solution, place in a constant temperature water bath at 45°C, alkalize for 45 minutes, add 280g of sodium hypochlorite, react at a constant temperature for 8 hours, add 8g of sodium bisulfite, neutralize with alkali, and obtain oxidized sweet potato starch after aqueous drying.
[0028] 4-Nitrobenzenephosphonium dichloride, CAS number is 777-52-6.
[0029] 4-Nitroaniline, CAS number is 100-01-6.
[0030] 3,3'-Iminodipropionic acid, CAS number is 505-47-5.
[0031] Example 1
[0032] (1) Under nitrogen atmosphere, 35 g of 4-nitrobenzene dichloride and 525 mL of acetonitrile were added to a reaction flask, and after stirring, 42 g of 4-nitroaniline and 38.5 g of triethylamine were added, and the mixture was reacted at 70° C. for 12 h. Dimethyl sulfoxide and deionized water were added to precipitate the mixture, and the mixture was filtered, washed with ethanol, and dried to obtain trinitrophenyl phosphorus nitrogen flame retardant monomer. The preparation reaction formula is as follows:
[0033]
[0034] (2) Under nitrogen atmosphere, 30 g of trinitrophenylphosphine nitrogen flame retardant monomer and 1050 mL of ethanol were added to the reaction flask, and after stirring evenly, 2.4 g of palladium carbon and 90 mL of hydrazine hydrate were added, and the mixture was reacted at 80° C. for 5 h, concentrated under reduced pressure, and recrystallized from ethanol to obtain triaminophenylphosphine nitrogen flame retardant monomer. The preparation reaction formula is as follows:
[0035]
[0036] (3) Under a nitrogen atmosphere, 25 g of triaminophenylphosphine flame retardant monomer and 200 mL of N,N-dimethylacetamide were added to a reaction flask, and after stirring, 17.5 g of 3,3'-iminodipropionic acid was added, and the mixture was reacted at 130° C. for 10 h, and concentrated under reduced pressure to obtain a hyperbranched polyamide polyamine crosslinking agent.
[0037] (4) 100 g of oxidized sweet potato starch and 250 mL of deionized water were placed in a three-necked flask, stirred evenly, and then 8 g of anhydrous sodium sulfate, 1 g of sodium hydroxide and 0.5 g of a hyperbranched polyamide polyamine crosslinking agent were added. The mixture was reacted at 50 °C for 4 h, the pH of the system was adjusted to neutral, and the mixture was filtered, washed, dried and crushed to obtain a hyperbranched crosslinked starch.
[0038] (5) 100 g of polypropylene powder and 30 g of hyperbranched cross-linked starch were mixed evenly, placed on a high-speed kneader for blending, the mixing temperature was 180°C, the screw speed was 90 r / min, the screw diameter was 12 mm, and added to a twin-screw extruder for extrusion granulation, the temperature of zone 1 was 185°C, zone 2 was 190°C, zones 3 and 4 were 195°C, zone 5 was 190°C, the main engine speed was 12.5 r / min, the feed speed was 7.0 r / min, and then placed in an injection molding machine for injection molding, the injection molding machine melt cavity temperature was 190°C, and the injection time was 8 s to obtain a cross-linked starch-based biodegradable plastic.
[0039] Example 2
[0040] (1) Under a nitrogen atmosphere, 60 g of 4-nitrobenzene dichloride and 600 mL of acetonitrile were added to a reaction flask, and after stirring, 66 g of 4-nitroaniline and 54 g of triethylamine were added, and the mixture was reacted at 80° C. for 8 h. Dimethyl sulfoxide and deionized water were added to precipitate the mixture, and the mixture was filtered, washed with ethanol, and dried to obtain a trinitrophenyl phosphorus nitrogen flame retardant monomer.
[0041] (2) Under a nitrogen atmosphere, 50 g of trinitrophenylphosphine nitrogen flame retardant monomer and 1250 mL of ethanol were added to a reaction flask. After stirring evenly, 2.5 g of palladium carbon and 125 mL of hydrazine hydrate were added. The mixture was reacted at 90 °C for 3 h, concentrated under reduced pressure, and recrystallized from ethanol to obtain triaminophenylphosphine nitrogen flame retardant monomer.
[0042] (3) Under a nitrogen atmosphere, 45 g of triaminophenylphosphine flame retardant monomer and 225 mL of N,N-dimethylacetamide were added to a reaction flask, and after stirring, 29.25 g of 3,3'-iminodipropionic acid was added, and the mixture was reacted at 140° C. for 5 h, and concentrated under reduced pressure to obtain a hyperbranched polyamide polyamine crosslinking agent.
[0043] (4) 100 g of oxidized sweet potato starch and 200 mL of deionized water were placed in a three-necked flask, stirred evenly, and then 7 g of anhydrous sodium sulfate, 0.8 g of sodium hydroxide and 1 g of a hyperbranched polyamide polyamine crosslinking agent were added. The mixture was reacted at 60 °C for 2 h, the pH of the system was adjusted to neutral, and the mixture was filtered, washed, dried and crushed to obtain a hyperbranched crosslinked starch.
[0044] (5) 100 g of polypropylene powder and 35 g of hyperbranched cross-linked starch were mixed uniformly, placed on a high-speed kneader for blending, the mixing temperature was 190°C, the screw speed was 100 r / min, the screw diameter was 15 mm, and added to a twin-screw extruder for extrusion granulation, the temperature of zone 1 was 185°C, zone 2 was 190°C, zones 3 and 4 were 195°C, zone 5 was 190°C, the main engine speed was 12.5 r / min, the feed speed was 7.0 r / min, and then placed in an injection molding machine for injection molding, the injection molding machine melt cavity temperature was 200°C, and the injection time was 5 s to obtain a cross-linked starch-based biodegradable plastic.
[0045] Example 3
[0046] (1) Under nitrogen atmosphere, 30 g of 4-nitrobenzene phosphorus dichloride and 600 mL of acetonitrile were added to a reaction flask, and after stirring, 37.5 g of 4-nitroaniline and 36 g of triethylamine were added, and the mixture was reacted at 65° C. for 16 h. Dimethyl sulfoxide and deionized water were added to precipitate the mixture, and the mixture was filtered, washed with ethanol, and dried to obtain a trinitrophenyl phosphorus nitrogen flame retardant monomer.
[0047] (2) Under a nitrogen atmosphere, 25 g of trinitrophenylphosphine nitrogen flame retardant monomer and 1000 mL of ethanol were added to a reaction flask. After stirring evenly, 2.5 g of palladium carbon and 87.5 mL of hydrazine hydrate were added. The mixture was reacted at 75 °C for 8 h, concentrated under reduced pressure, and recrystallized from ethanol to obtain triaminophenylphosphine nitrogen flame retardant monomer.
[0048] (3) Under a nitrogen atmosphere, 20 g of triaminophenylphosphine flame retardant monomer and 200 mL of N,N-dimethylacetamide were added to a reaction flask, and after stirring, 18 g of 3,3'-iminodipropionic acid was added, and the mixture was reacted at 125° C. for 12 h, and concentrated under reduced pressure to obtain a hyperbranched polyamide polyamine crosslinking agent.
[0049] (4) 100 g of oxidized sweet potato starch and 350 mL of deionized water were placed in a three-necked flask, stirred evenly, and then 10 g of anhydrous sodium sulfate, 1.2 g of sodium hydroxide and 1.5 g of a hyperbranched polyamide polyamine crosslinking agent were added. The mixture was reacted at 45 °C for 5 h, the pH of the system was adjusted to neutral, and the mixture was filtered, washed, dried and crushed to obtain a hyperbranched crosslinked starch.
[0050] (5) 100 g of polypropylene powder and 40 g of hyperbranched cross-linked starch were mixed evenly, placed on a high-speed kneader for blending, the mixing temperature was 175°C, the screw speed was 80 r / min, the screw diameter was 15 mm, and added to a twin-screw extruder for extrusion granulation, the temperature of zone 1 was 185°C, zone 2 was 190°C, zones 3 and 4 were 195°C, zone 5 was 190°C, the main engine speed was 12.5 r / min, the feed speed was 7.0 r / min, and then placed in an injection molding machine for injection molding, the injection molding machine melt cavity temperature was 180°C, and the injection time was 10 s to obtain a cross-linked starch-based biodegradable plastic.
[0051] Example 4
[0052] (1) Under a nitrogen atmosphere, 42 g of 4-nitrobenzene dichloride and 630 mL of acetonitrile were added to a reaction flask, and after stirring, 48.3 g of 4-nitroaniline and 46.2 g of triethylamine were added, and the mixture was reacted at 70° C. for 15 h. Dimethyl sulfoxide and deionized water were added to precipitate the mixture, and the mixture was filtered, washed with ethanol, and dried to obtain a trinitrophenyl phosphorus nitrogen flame retardant monomer.
[0053] (2) Under a nitrogen atmosphere, 35 g of trinitrophenylphosphine nitrogen flame retardant monomer and 1260 mL of ethanol were added to a reaction flask. After stirring evenly, 2.8 g of palladium carbon and 112 mL of hydrazine hydrate were added. The mixture was reacted at 85 °C for 5 h, concentrated under reduced pressure, and recrystallized from ethanol to obtain triaminophenylphosphine nitrogen flame retardant monomer.
[0054] (3) Under a nitrogen atmosphere, 28 g of triaminophenylphosphine flame retardant monomer and 240 mL of N,N-dimethylacetamide were added to a reaction flask, and after stirring, 18.2 g of 3,3'-iminodipropionic acid was added, and the mixture was reacted at 135° C. for 10 h, and concentrated under reduced pressure to obtain a hyperbranched polyamide polyamine crosslinking agent.
[0055] (4) 100 g of oxidized sweet potato starch and 300 mL of deionized water were placed in a three-necked flask, stirred evenly, and then 9 g of anhydrous sodium sulfate, 1.1 g of sodium hydroxide and 2 g of a hyperbranched polyamide polyamine crosslinking agent were added. The mixture was reacted at 55 °C for 5 h, the pH of the system was adjusted to neutral, and the mixture was filtered, washed, dried and crushed to obtain a hyperbranched crosslinked starch.
[0056] (5) 100 g of polypropylene powder and 45 g of hyperbranched cross-linked starch were mixed evenly, placed on a high-speed kneader for blending, the mixing temperature was 185°C, the screw speed was 90 r / min, the screw diameter was 13 mm, and added to a twin-screw extruder for extrusion granulation, the temperature of zone 1 was 185°C, zone 2 was 190°C, zones 3 and 4 were 195°C, zone 5 was 190°C, the main engine speed was 12.5 r / min, the feed speed was 7.0 r / min, and then placed in an injection molding machine for injection molding, the injection molding machine melt cavity temperature was 195°C, and the injection time was 8 s to obtain a cross-linked starch-based biodegradable plastic.
[0057] Example 5
[0058] (1) Under nitrogen atmosphere, 20 g of 4-nitrobenzene dichloride and 300 mL of acetonitrile were added to a reaction flask, and after stirring, 24 g of 4-nitroaniline and 22 g of triethylamine were added, and the mixture was reacted at 80° C. for 16 h. Dimethyl sulfoxide and deionized water were added to precipitate the mixture, and the mixture was filtered, washed with ethanol, and dried to obtain a trinitrophenyl phosphorus nitrogen flame retardant monomer.
[0059] (2) Under a nitrogen atmosphere, 16 g of trinitrophenylphosphine nitrogen flame retardant monomer and 560 mL of ethanol were added to a reaction flask. After stirring evenly, 1.36 g of palladium carbon and 45.6 mL of hydrazine hydrate were added. The mixture was reacted at 90 °C for 8 h, concentrated under reduced pressure, and recrystallized from ethanol to obtain triaminophenylphosphine nitrogen flame retardant monomer.
[0060] (3) Under a nitrogen atmosphere, 12 g of triaminophenylphosphine flame retardant monomer and 95 mL of N,N-dimethylacetamide were added to a reaction flask, and after stirring, 10.5 g of 3,3'-iminodipropionic acid was added, and the mixture was reacted at 130° C. for 12 h, and concentrated under reduced pressure to obtain a hyperbranched polyamide polyamine crosslinking agent.
[0061] (4) 100 g of oxidized sweet potato starch and 280 mL of deionized water were placed in a three-necked flask, stirred evenly, and then 8 g of anhydrous sodium sulfate, 0.9 g of sodium hydroxide and 2.5 g of a hyperbranched polyamide polyamine crosslinking agent were added. The mixture was reacted at 55 °C for 5 h, the pH of the system was adjusted to neutral, and the mixture was filtered, washed, dried and crushed to obtain a hyperbranched crosslinked starch.
[0062] (5) 100 g of polypropylene powder and 50 g of hyperbranched cross-linked starch were mixed evenly, placed on a high-speed kneader for blending, the mixing temperature was 180°C, the screw speed was 100 r / min, the screw diameter was 15 mm, and added to a twin-screw extruder for extrusion granulation, the temperature of zone 1 was 185°C, zone 2 was 190°C, zones 3 and 4 were 195°C, zone 5 was 190°C, the main engine speed was 12.5 r / min, the feed speed was 7.0 r / min, and then placed in an injection molding machine for injection molding, the injection molding machine melt cavity temperature was 200°C, and the injection time was 10 s to obtain a cross-linked starch-based biodegradable plastic.
[0063] Comparative Example 1
[0064] (1) 100 g of oxidized sweet potato starch and 250 mL of deionized water were placed in a three-necked flask, stirred evenly, and then 8 g of anhydrous sodium sulfate, 1 g of sodium hydroxide and 0.5 g of triaminophenylphosphine nitrogen flame retardant monomer (prepared in Example 1) were added, reacted at 50° C. for 4 h, the pH of the system was adjusted to neutral, filtered, washed, dried and crushed to obtain cross-linked starch.
[0065] (2) 100 g of polypropylene powder and 30 g of cross-linked starch were mixed evenly, placed on a high-speed kneader for blending, the mixing temperature was 180°C, the screw speed was 90 r / min, the screw diameter was 12 mm, and added to a twin-screw extruder for extrusion granulation, the temperature of zone 1 was 185°C, zone 2 was 190°C, zones 3 and 4 were 195°C, zone 5 was 190°C, the main engine speed was 12.5 r / min, the feed speed was 7.0 r / min, and then placed in an injection molding machine for injection molding, the injection molding machine melt cavity temperature was 190°C, and the injection time was 8 s to obtain a cross-linked starch-based biodegradable plastic.
[0066] Comparative Example 2
[0067] (1) 100 g of oxidized sweet potato starch and 250 mL of deionized water were placed in a three-necked flask, stirred evenly, and then 8 g of anhydrous sodium sulfate, 1 g of sodium hydroxide and 0.5 g of sodium hexametaphosphate were added. The mixture was reacted at 50 °C for 4 h, the pH of the system was adjusted to neutral, and the mixture was filtered, washed, dried and crushed to obtain cross-linked starch.
[0068] (2) 100 g of polypropylene powder and 30 g of cross-linked starch were mixed evenly, placed on a high-speed kneader for blending, the mixing temperature was 180°C, the screw speed was 90 r / min, the screw diameter was 12 mm, and added to a twin-screw extruder for extrusion granulation, the temperature of zone 1 was 185°C, zone 2 was 190°C, zones 3 and 4 were 195°C, zone 5 was 190°C, the main engine speed was 12.5 r / min, the feed speed was 7.0 r / min, and then placed in an injection molding machine for injection molding, the injection molding machine melt cavity temperature was 190°C, and the injection time was 8 s to obtain a cross-linked starch-based biodegradable plastic.
[0069] Comparative Example 3
[0070] 100g of polypropylene powder and 30g of oxidized sweet potato starch were mixed evenly, placed on a high-speed kneader for blending, the mixing temperature was 180°C, the screw speed was 90r / min, the screw diameter was 12mm, and added to a twin-screw extruder for extrusion granulation, the temperature of zone one was 185°C, zone two was 190°C, zones three and four were 195°C, zone five was 190°C, the main engine speed was 12.5r / min, the feeding speed was 7.0r / min, and then placed in an injection molding machine for injection molding, the injection molding machine melt cavity temperature was 190°C, and the injection time was 8s to obtain a starch-based biodegradable plastic.
[0071] Limiting oxygen index test: Refer to standard GB / T 2406-2008 and use oxygen index meter to carry out limiting oxygen index test.
[0072] Vertical combustion level test: refer to standard GB / T 2408-1996 and use horizontal vertical combustion instrument for testing.
[0073] Table 1 Flame retardant performance test
[0074]
[0075] It can be seen from the test results in the above table that with the increase of the content of hyperbranched cross-linked starch, the flame retardant properties of the cross-linked starch-based biodegradable plastics are gradually enhanced. The limiting oxygen index in Example 5 reaches 33.0%, and the vertical combustion grade is V-0, which belongs to the level of flame-retardant materials; this is because the hyperbranched cross-linked starch is a three-dimensional tree-like hyperbranched macromolecule, and the multiple amino groups in its structure can undergo a grafting reaction with the aldehyde groups on the surface of the oxidized sweet potato starch to form a dense three-dimensional cross-linked spatial network structure, so that the starch is tightly connected together, and its structure contains phosphorus and nitrogen synergistic flame retardant elements, which can be used in the process of its thermal degradation. Polyphosphoric acid is produced and covers the surface of the polymer matrix. At the same time, a large number of terminal amino groups decompose under heat to produce NH3, which causes the matrix to expand. A large number of substances with benzene ring structures undergo cross-linking reactions to form a high-strength carbon layer with a graphite structure similar to that of an aromatic ring structure bridged by POP bonds. This can bind a large amount of gas produced during the combustion process, so that the matrix will not expand excessively and produce cracks during the combustion process. In addition, this compact and stable carbon layer can effectively isolate the unburned matrix from contact with external heat sources, hinder heat exchange between the matrix and the outside world, thereby inhibiting continued combustion of the polymer and improving flame retardant properties.
[0076] The cross-linking agent in the comparative example is a triaminobenzene phosphorus nitrogen flame retardant monomer, which does not have a hyperbranched structure and has a limited degree of cross-linking, but contains phosphorus nitrogen flame retardant elements and has a certain flame retardant effect; the cross-linking agent in comparative example 2 is the commonly used sodium metaphosphate, which only contains phosphorus elements and has a limited flame retardant effect; the starch in comparative example 3 is not cross-linked, has a relatively loose structure, has poor compatibility with the polypropylene matrix, and does not have flame retardant properties.
[0077] Tensile performance test: refer to the second part of the standard GB / T 1040.2-2006 Determination of tensile properties of plastics. The tensile test is carried out on an electronic universal testing machine with a tensile speed of 50mm / min. The average value of the test data of 5 specimens is taken as the test result.
[0078] Impact resistance test: refer to GB / T 16420-2006 Plastic impact performance small sample test method, test on a simply supported beam impact testing machine, and take the average value of 5 sample test data as the test result.
[0079] Table 2 Mechanical properties test
[0080] Tensile strength(MPa) <![CDATA[Impact strength (KJ / m 2 )]]> Example 1 9.18 3.52 Example 2 9.95 4.01 Example 3 10.74 4.35 Example 4 11.52 4.64 Example 5 11.68 4.87 Comparative Example 1 8.01 3.24 Comparative Example 2 7.33 2.83 Comparative Example 3 6.95 2.55
[0081] From the test results in the above table, it can be seen that with the increase of the content of hyperbranched cross-linked starch, the mechanical properties of the cross-linked starch-based biodegradable plastics are gradually enhanced, wherein the tensile strength in Example 4 is 11.52 MPa, and the impact strength is 4.64 KJ / m 2This is because the hyperbranched polyamide polyamine cross-linking agent itself has good mechanical properties, and can significantly enhance the strength of the material after cross-linking with starch. The multiple amino groups in its structure can cross-link with the aldehyde groups on the surface of oxidized sweet potato starch. The degree of cross-linking increases, making the molecular chains more tightly arranged, the porosity decreases, the hydrophilicity of starch weakens, and the compatibility with polypropylene materials increases, the binding force increases, and the material can absorb more impact energy when subjected to external forces, thereby enhancing the mechanical properties of the plastic.
[0082] Water absorption test: refer to GB / T 1034-2008 test method for water absorption performance of plastics, cut the cross-linked starch-based biodegradable plastic into specified sizes, weigh its initial mass m1, place it in a container filled with distilled water, soak it for 48 hours, quickly wipe off all the water on the surface of the sample with filter paper, and weigh its mass m2 again. Water absorption = (m2-m1) / m1×100%.
[0083] Table 3 Water resistance test
[0084] Water absorption (%) Example 1 2.91 Example 2 2.24 Example 3 1.65 Example 4 1.12 Example 5 0.83 Comparative Example 1 4.34 Comparative Example 2 5.21 Comparative Example 3 12.36
[0085] It can be seen from the test results in the above table that with the increase of the content of hyperbranched cross-linked starch, the water absorption rate of the cross-linked starch-based biodegradable plastic gradually decreases, and the water absorption rate in Example 5 is only 0.83%. This is because the increase in the degree of cross-linking promotes the combination of starch and polypropylene, increases the overall hydrophobicity of the material, reduces the water absorption rate of the plastic, and thus can maintain the stability of size and mechanical properties, which is very beneficial for various applications.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a cross-linked starch-based biodegradable plastic, characterized in that: The preparation method is carried out according to the following steps: Step (1), placing oxidized sweet potato starch and deionized water in a three-necked flask, stirring evenly, adding anhydrous sodium sulfate, sodium hydroxide and a hyperbranched polyamide polyamine crosslinking agent, stirring to react, and after the reaction is completed, adjusting the pH of the system to neutral, filtering, washing, drying and crushing to obtain a hyperbranched crosslinked starch; Step (2), mixing the polypropylene powder and the hyperbranched cross-linked starch uniformly, placing them on a high-speed kneader for blending, the mixing temperature is 175-190° C., the screw speed is 80-100 r / min, the screw diameter is 10-15 mm, adding them to a twin-screw extruder for extrusion granulation, and then placing them in an injection molding machine for injection molding, the injection molding machine melt chamber temperature is 180-200° C., and the injection time is 5-10 s, to obtain a cross-linked starch-based biodegradable plastic; In the step (1), the ratio of oxidized sweet potato starch, deionized water, anhydrous sodium sulfate, sodium hydroxide, and hyperbranched polyamide polyamine crosslinking agent is 100 g: (200-350) mL: (7-10) g: (0.8-1.2) g: (0.5-2.5) g; In step (1), the reaction temperature is 45-60° C. and the reaction time is 2-5 h; In the step (2), the ratio of polypropylene powder to hyperbranched cross-linked starch is 100 g: (30-50) g; The preparation method of the hyperbranched polyamide polyamine crosslinking agent in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add 4-nitrobenzene phosphorus dichloride and acetonitrile to a reaction flask, stir evenly, then add 4-nitroaniline and triethylamine, stir to react, after the reaction is completed, add dimethyl sulfoxide and deionized water to precipitate, filter, wash with ethanol, and dry to obtain a trinitrophenyl phosphorus nitrogen flame retardant monomer; Step S2, under a nitrogen atmosphere, add trinitrophenylphosphine nitrogen flame retardant monomer and ethanol to a reaction flask, stir evenly, add palladium carbon and hydrazine hydrate, react at 75-90° C. for 3-8 hours, concentrate under reduced pressure, and recrystallize from ethanol to obtain triaminophenylphosphine nitrogen flame retardant monomer; Step S3, under a nitrogen atmosphere, add triaminophenylphosphine flame retardant monomer and N,N-dimethylacetamide to a reaction flask, stir evenly, add 3,3'-iminodipropionic acid, react at 125-140° C. for 2-4 h, then react at 160-180° C. for 5-12 h, and concentrate under reduced pressure to obtain a hyperbranched polyamide polyamine crosslinking agent; In the step S1, the ratio of 4-nitrobenzene phosphorus dichloride, acetonitrile, 4-nitroaniline and triethylamine is 1 g: (10-20) mL: (1.1-1.25) g: (0.9-1.2) g; In step S1, the reaction temperature is 65-80°C and the reaction time is 8-16h; In the step S2, the ratio of trinitrophenylphosphine nitrogen flame retardant monomer, ethanol, palladium carbon, and hydrazine hydrate is 1 g: (25-40) mL: (0.05-0.1) g: (2.5-3.5) mL; In the step S3, the ratio of triaminophenylphosphine nitrogen flame retardant monomer, N,N-dimethylacetamide and 3,3'-iminodipropionic acid is 1 g: (5-10) mL: (0.65-0.9) g.
Citation Information
Patent Citations
Method for preparing polyamide amine tree-shaped macromolecule grafted starch-based carrier
CN102151555A
Hyperbranched polyamide composite filled polymer-based thermal conductive plastic and preparation method thereof
CN104177842A